Anger management [emotion recognition]. - Cherry, S.
Aside from monitoring calls for quality assurance purposes, many corporate call centers require call monitoring for anger management. By identifying angry emotions in calls, managers can take appropriate action against call agents who may have behaved improperly. NICE Systems Inc., a supplier of call monitoring systems, has developed an emotion-sensitive software that is able to detect angry emotions during phone conversations using the changes in a voice's pitch. The software engine will go over the data signal, and, second by second, run the algorithm. If emotion is detected, a report is generated that includes the level of certainty that the call included angry emotions. As the software improves and the hardware gets faster, ever more calls will be scanned in ever more sophisticated ways.
Keywords: Angry emotions; Call agents; Call monitoring; Corporate call centers; Emotion detection; Emotion recognition; Emotion-sensitive software